Menakar Tujuan Hukum dibalik Putusan MA No. 46 P/HUM/2018 Yang Pro Koruptor - Nurlindah Nurlindah; A. Sugirman; Rosita Rosita (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2019)
In welcoming 2019 concurrent general elections, the General Election Commission issued PKPU No. 20 of 2018, one of which banned former convicts of corruption from becoming legislative candidates on the grounds that corruption is an extraordinary offense that is commonly practiced by legislators both individually and in congregation. The regulation is stated in Article 4 paragraph (3) PKPU No. 20 of 2018 concerning Nominations for Members of DPR, Provincial DPRD and Regency / City DPRD. However, the regulation was canceled with the issuance of Supreme Court decision No. 46 P / HUM / 2018. Based on this, the limitation of the problem of this research is how to measure the aspects of the legal objectives behind the decision No. 46 P / HUM / 2018 which are more pro-corrupt so that they can understand the judge's decidendi ratio in canceling the prohibition of ex-convicts from becoming legislators. This type of research is normative legal research with a statutory approach and conceptual approach. The theoretical basis in the presentation of research results is the theory of legal goals by Gustav Radbruch namely justice, certainty and usefulness which is compared with Islamic law. The results of this study indicate that the Supreme Court's consideration overturned PKPU No. 20 of 2018 because it is considered contrary to Article 240 of Law No. 7 of 2017 concerning General Elections and Article 12 of Law No. 12 of 2011 concerning Formation of Laws and Regulations. The Supreme Court's considerations in the a quo ruling contain the three legal objectives. However, it is more inclined to legal certainty, so it does not reflect the value of justice that lives in the community. The cause of not achieving the values of justice that live in the community in the a quo decision is because the basis for testing the regulation is Law No. 7 of 2017 concerning General Elections does not prohibit such matters, even though the nomination rules on the executive body namely the President and Vice President require that they do not have a bad track record. Likewise when viewed from Islamic law which requires legislative candidates called ahlul ahli wal aqdi must have a fair way which means having integrity and a good image in the society.